Protective Factors for Psychological Distress in Hospital Staff during the Coronavirus Pandemic - Shirzad, Boshra; Kianimoghadam, Amir Sam; Tajik, Maryam; Bakhtiari, Maryam (Researcher Bulletin of Medical Sciences, 2024)
Objective: The hospital staff are at-risk for the development of Psychological Distress (PD) during and after the COVID-19 pandemic. The aim of the current study was to investigate three factors, including coping, resilience, and spiritual well-being as protective factors for the development of PD among hospital staff during the COVID-19 pandemic. Materials and Methods: In the current research, convenience sampling method was used to select 300 hospital staff from various hospitals in Tehran. The study sample filled up a number of measures, namely Kessler Psychological Distress Scale (K-10), Brief Resilience Scale (BRS), Life Paths Measurement Packet Coping Scale, and Spiritual Well-being Questionnaire (SWB). The collected data were analyzed using multiple statistical methods. Results: The findings revealed that nearly 40 percent of the study sample experienced a severe mental disorder (N=114), while nearly 30 percent of them experienced a moderate mental disorder (N=74). The results of the Pearson’s correlation coefficient revealed that PD was significantly and negatively correlated with resilience. Also, the study findings showed that there was a significant positive correlation between various aspects of spiritual well-being among hospital staff. Conclusion: The findings of the current study suggested that the three factors of coping, resilience, and spiritual well-being may have a minimal protective role in PD development among the hospital staff population. More research is necessary in order to draw a conclusion on the role of these variables with regard to PD. It is essential to conduct more studies in this area in order to develop useful interventions and strategies to support this at-risk population in such a difficult situation, which puts them at a high risk for PD development.